2021
DOI: 10.1002/cbic.202000679
|View full text |Cite
|
Sign up to set email alerts
|

The Peculiar Case of the Hyper‐thermostable Pyrimidine Nucleoside Phosphorylase from Thermus thermophilus**

Abstract: The poor solubility of many nucleosides and nucleobases in aqueous solution demands harsh reaction conditions (base, heat, cosolvent) in nucleoside phosphorylase-catalyzed processes to facilitate substrate loading beyond the low millimolar range. This, in turn, requires enzymes that can withstand these conditions. Herein, we report that the pyrimidine nucleoside phosphorylase from Thermus thermophilus is active over an exceptionally broad pH (4-10), temperature (up to 100°C) and cosolvent space (up to 80 % (v/… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…Similarly, no conversion was observed under reaction conditions outside of the working space of TtPyNP (pH 3 or pH 12, Figure 1A). [26] NMR analysis of a reaction mixture with TtPyNP and 1a corroborated the proposed reactivity and creation of the pentose-1-phosphate 3, as evident from the rise of an additional 1 H NMR signal at 5.57 ppm showing a strong H,P-HMQC signal (Figure 1B). Consistent with the native reactivity of PyNPs, inversion at the anomeric position was evident by this signal lacking NOE contacts to the 4ʹ-methyl group of 3, while the corresponding anomeric proton in 1a showed clear correlation to the methyl substituent.…”
supporting
confidence: 65%
See 3 more Smart Citations
“…Similarly, no conversion was observed under reaction conditions outside of the working space of TtPyNP (pH 3 or pH 12, Figure 1A). [26] NMR analysis of a reaction mixture with TtPyNP and 1a corroborated the proposed reactivity and creation of the pentose-1-phosphate 3, as evident from the rise of an additional 1 H NMR signal at 5.57 ppm showing a strong H,P-HMQC signal (Figure 1B). Consistent with the native reactivity of PyNPs, inversion at the anomeric position was evident by this signal lacking NOE contacts to the 4ʹ-methyl group of 3, while the corresponding anomeric proton in 1a showed clear correlation to the methyl substituent.…”
supporting
confidence: 65%
“…Interestingly, the apparent Michalis-Menten constant KMʹ of the phosphorolysis of 1a (KMʹ = 3.37 mM) indicated that TtPyNP has a much lower affinity for 1a compared to natural nucleosides like uridine or thymidine (KM < 1 mM), [27] suggesting that productive binding of the modified substrate 1a might present a challenge due to the increased steric bulk. In addition to a lower affinity for 1a, TtPyNP also displayed a lower rate constant compared to uridine (0.59 vs 5.05 s -1 for 1 mM substrate at 60 °C and pH 9) [26] which showed a similar temperature-dependence as indicated by phosphorolysis experiments at different temperatures monitored by UV spectroscopy (Figure 1D). [29,30] Collectively, these results demonstrate that, unlike other nucleoside phosphorylases, TtPyNP selectively converts the 4ʹ-methylated nucleoside 1a to the corresponding sugar phosphate 3, albeit with a lower rate constant and substrate affinity compared to the native substrates.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…[29] While purine NPs have been researched intensively, [30][31][32][33][34][35][36] including their ratetemperature relationships, [10,37] comparably little is known about rate-temperature relationships of reactions catalyzed by the structurally distinct pyrimidine NPs. [38] Since these enzymes typically operate across a wide pH window with similar rate constants [39,40] and convert electronically diverse substrates, [38,39] we hypothesized that they would present a convenient model system to interrogate pH and deprotonation effects on the Eyring plots of nucleoside phosphorolysis, as an example of a simple nucleophilic substitution. Thus, we questioned if there exists an activation heat capacity change during the phosphorolysis reactions catalyzed by thermostable pyrimidine NPs and, if so, whether this effect shows any pH-and/or protonationdependence across the broad working space of these enzymes.…”
mentioning
confidence: 99%